Probability Distribution of Magnetic Field Strengths through the Cyclotron Lines in High-Mass X-ray Binaries - A. Taani; A. Abushattal; A. Khasawneh; N. Almusleh; M. AlWardat (Jordan Journal of Physics, 2025)
The study of variation of measured cyclotron lines is of fundamental importance to understand the physics of the accretion process in magnetized neutron star systems. We investigate the magnetic field formation, evolution and distribution for several High- Mass X-ray Binaries (HMXBs). We focus our attention on the cyclotron lines that have been detected in HMXB classes in their X-ray spectra. As has been correctly pointed out, several sources show variation in cyclotron lines, which can result due to the effect of accretion dynamics and hence that would reflect the magnetic field characteristics. Besides, the difference in time scales of variation of accretion rate and different types of companion can be used to distinguish between magnetized neutron stars. Keywords:Stars: neutron stars, High-Mass X-ray binaries, Stars: magnetic field, Cyclotron lines.